Identifying extensions required by RUP (Rational Unified Process) to comply with CMM (Capability Maturity Model) levels 2 and 3 - Manzoni, Lisandra Vielmo (2011)
This paper describes an assessment of the Rational Unified Process (RUP) based on the Capability Maturity Model (CMM). For each key practice (KP) identified in each key process area (KPA) of CMM levels 2 and 3, the Rational Unified Process was assessed to determine whether it satisfied the KP or not. For each KPA, the percentage of the key practices supported was calculated, and the results were tabulated. The report includes considerations about the coverage of each key process area, describing the highlights of the Rational Unified Process regarding its support for CMM levels 2 and 3, and suggests where an organization using it will need to complement it to conform to CMM. The assessment resulted in the elaboration of proposals to enhance the Rational Unified Process in order to satisfy the key process areas of CMM. Some of these are briefly described in this article.